Novel surgical approach: compare the efficacy of vaginal hysterectomy with abdominal hysterectomy in non-descent uterus - Alwani, Madhuri; Srivastava, Ishan; Thakur, Ratna; Kaur, Ravjyot; Pathak, Shruti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The aim of the study was to compare the efficacy of vaginal hysterectomy with that of abdominal hysterectomy in non-descent uterus for safety and feasibility of advancing gynaecological practice. Methods: This prospective observational study was conducted in the Department of Obstetrics and Gynaecology, Sri Aurobindo Medical College and Postgraduate Institute, Indore (M.P.) from October 2013 to April 2015. A total of 170 cases were enrolled in this study. Subjects were equally divided into two groups of equal size and assigned to a specified group i.e. study and control group. Each group consists of 85 cases. Results: The two techniques of intervention measured a highly significant mean difference for parameters such as ambulation (1.75), need of analgesic doses post-operative (2.80), resumption of bowel/bladder activity (8.62) and hospital stay (4.44) were less in study group when compared to control group where in ambulation (2.25), need of analgesic doses post-operative (5.11), resumption of bowel/bladder activity (18.75) and hospital stay (6.96). It was also observed that vaginal discharge (4.7%), UTI (4.7%) and re-hospitalization (2.4%) were less in study group when compared to control group which showed vaginal discharge (4%), UTI (0%) and re-hospitalization (5%). Vaginal hysterectomy in women with non-descent and moderately enlarged uteri is safe. A combination of debulking techniques is often needed and the surgeon needs to be familiar with them. With experience larger uterus can be removed. Thus this scar less approach should be chosen as a preferred method for hysterectomy. Conclusions: This study showed UA-S/D ratio and UA-RI>2SD are significant predictors of perinatal deaths and immediate neonatal resuscitation in preeclampsia. Acute fetal distress in labour or neonatal nursery admission could not be predicted.